PENGEMBANGAN DATABASE MIKROORGANISME INDIGENOS INDONESIA - Sjamsuridzal, Wellyzar; Oetari, Ariyanti; Hertono, Gatot F.; Sitaresmi, Sitaresmi (Makara Journal of Science, 2006)
Development of Database for Indigenous Indonesian Microorganisms. The objective of the research is to create and develop a database of indigenous Indonesian microorganisms based at the University of Indonesia. Development of the database of indigenous Indonesian microorganisms was carried out in several stages, i.e. data identification, database design, programming, data entry, testing and debugging, and repairing and maintenance. Development of the database utilized the licensed software of General Public License (GPL), which include Linux RedHat 9.0 (operating system), Apache ver. 2.20 (web server), MySQL ver. 4.2 (database server), and PHP ver. 4.3 (web interface programming language). The result of this research is a database named UI Bioinfo which has the following facilities: online catalog search for UICC (University of Indonesia Culture Collection) strains collection and sequence homology search utility through BLAST (Basic Local Alignment Search Tool). Integrated information on strains collection was first carried out on the yeast collection. At present, UI Bioinfo contains information for 297 strains that includes isolation data, morphological descriptions, physiology-biochemical characteristics, and images. Moreover it also contains sequence data from the large subunit (LSU) ribosomal RNA gene and the internal transcribed spacer (ITS) regions. UI Bioinfo can be accessed from the following site: http://152.118.162.250/bio/. Future development will be addition of data from the other collections in UICC